The performance of the community health workers of the city of Teresina/Piauí concerning hanseníase - Danielle Yasmin Moura Lopes de Araújo; Jaciara Sousa Andrade; Maria Zélia de Araújo Madeira (Rev Rene)
Hanseníase is an infectious-contagious illness whose control is a great challenge. In this context, the community health workers (CHW) play a basic role since they establish a bond between the community and the services of health. We aimed to analyze the performance of the CHW from Teresina/PI on Hanseníase. It is about a cross sectional study, of quantitative approach. For data collection a questionnaire with closed questions about the performance of the CHW, was applied to 178 CHW, north-central area of Teresina, in April 2010. The results show that 94.38% of the CHW guide some kind of prevention measure. The most cited one was the guiding for the Basic Unit of Health (78.92%); 61.24% guide auto-care measures, being the care with eyes and nose mentioned by 11,93% and 14,68% of those, respectively. Therefore, it is evidenced that the performance of the CHW on Hanseníase does not follow the recommendations of the Health department, being insufficient and sometimes incorrect.